The synergistic and antagonistic antioxidant interactions of dietary phytochemical combinations. Issue 20 (13th November 2022) - Chen, Xuan; Li, Hongyan; Zhang, Bing; Deng, Zeyuan
Abstract: The frequent intake of whole foods and dietary food variety is recommended due to their health benefits, such as prevention of multiple chronic diseases, including cancer, Alzheimer's disease, cardiovascular diseases, and type 2 diabetes mellitus. Often, consuming whole fruits or vegetables showed the enhanced effects than consuming the individual dietary supplement from natural products, which is widely explained by the interactive effects of co-existing phytochemicals in whole foods. Although research relevant to interactive effects among the bioactive compounds mounted up, the mechanism of interaction is still not clear. Especially, biological influence factors such as bioavailability are often neglected. The present review summarizes the progress on the synergistic and antagonistic effects of dietary phytochemicals, the evaluating models for antioxidant interactions, and the possible interaction mechanisms both in vitro and in vivo, and with an emphasis on biological-related molecular mechanisms of phytochemicals. The research on the interaction mechanism is of value for guiding how to take advantage of synergistic effects and avoid antagonistic effects in daily diets or phytochemical-based treatments for preventing chronic diseases.